Employee satisfaction and digitalization of working method in National Bank Limited: A study on Agrabad branch employees - Sammi, Tabassum (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.